The Inhibitor of Prothrombin Conversion in Plasma of Patients on Oral Anticoagulant Treatment - Bertina, R M; Westhoek-Kuipers, M E J; Alderkamp, G H J (Thrombosis and Haemostasis, 1981)
Pooled plasma of patients under stable oral anticoagulation has been analysed with respect to the presence of the vitamin-K dependent factors (factors II, VII, IX and X). Of all factors 1.5-2 times more antigen than procoagulant activity was present. The concentration of factors II, X (measured spectrophotometrically) and VII is about 0.25 U/ml while factor IX is slightly higher. Coagulation assays of factor X always gave lower values than the spectrophotometric assay. This discrepancy was not influenced by the removal of either factor II-factor VII- or factor IX antigen. However, when the factor X antigen was replaced by normal factor X, all factor X assays gave identical results, indicating that PIVKA X is responsible for these discrepancies. Using the technic of the Thrombotest-dilution curve it was shown that PIVKA X is the factor that causes the abnormal prolongation of ox-brain prothrombin time in these plasmas.
Keywords: Oral anticoagulation; PIVKA X; Inhibitor